Effectiveness of the guava leaf extracts against lipopolysaccharide-induced oxidative stress and immune responses in Cyprinus carpio. Issue 105 (October 2020) - Giri, Sib Sankar; Kim, Hyoun Joong; Kim, Sang Guen; Kim, Sang Wha; Kwon, Jun; Lee, Sung Bin; Sukumaran, V.; Chang Park, Se
Abstract: The anti-inflammatory activity of the guava leaf extracts (GLE) against LPS-induced inflammatory responses in fish macrophage cell lines is well documented. Here, we evaluated the effects of dietary GLE on LPS-induced oxidative stress, immune responses, and glucocorticoid receptor-related gene expression in Cyprinus carpio . Basal diet was supplemented with 0 (control), 100, 150, 200, or 250 mg kg −1  GLE for eight weeks. Highest ( p  < 0.05) weight gain rate was obtained in fish group supplemented with 200 mg kg −1 of GLE. The results showed that superoxide dismutase, glutathione-S-transferase, glutathione peroxidase, glutathione reductase, lysozyme, and complement C3 decreased, while malondialdehyde level increased in the liver and spleen upon LPS-challenge. Dietary GLE supplementation (especially 200 or 250 mg kg −1 ) alleviated LPS-induced changes. Similarly, GLE (150–250 mg kg −1 ) reversed LPS-induced alteration of serum biochemical parameters such as alkaline phosphatase, aspartate transaminase, alanine transaminase, and myeloperoxidase. LPS treatment markedly induced increased the mRNA levels of TNF-α, IL-1β, and NF-κB p65 in both the liver and kidney tissues; however, GLE pre-treatment attenuated LPS-induced elicitation of TNF-α, IL-β, and NF-κB p65. Moreover, dietary GLE supplementation significantly increased the expression of HSP70 and HSP90, and glucocorticoid receptor in the liver and kidney after LPS challenge. Thus, GLE attenuated LPS-induced inflammation response by up-regulating glucocorticoid receptor-related gene expression in carp. Finally, GLE supplementation reduced carp mortality after LPS-challenge. These results suggest that dietary supplementation with 200 mg kg −1  GLE is adequate for effectively attenuating LPS-induced oxidative stress and immune-suppressive effects in C. carpio . Highlights: Guava leaf extract (GLE) effectively prevented LPS-induced oxidative stress. GLE improved anti-oxidant activity and immune responses in Cyprinus carpio . GLE regulated inflammation -related gene expression in C. carpio . GLE conferred highest survival after LPS-challenge at 200 mg/kg.